Simple analytical solution for selective harmonic elimination technique. Issue 9 (4th April 2016) - Ahmed, M.; Hendawi, E.; Taha, I.B.M.
Abstract : A new simple analytical and closed‐form solution for the harmonic content injected in the five‐level inverters at low switching control technique is proposed. The equations of the fundamental and the third harmonic are formulated and solved. The switching angles have been calculated to fix the fundamental voltage at a specified value and cancel the third‐order harmonic. Two approaches have been proposed based on the modulation index. The proposed method can be feasible for a wide range of modulation index.